2014
DOI: 10.1155/2014/856592
|View full text |Cite
|
Sign up to set email alerts
|

Copper Oxide Nanomaterials Prepared by Solution Methods, Some Properties, and Potential Applications: A Brief Review

Abstract: Cupric oxide (CuO), having a narrow bandgap of 1.2 eV and a variety of chemophysical properties, is recently attractive in many fields such as energy conversion, optoelectronic devices, and catalyst. Compared with bulk material, the advanced properties of CuO nanostructures have been demonstrated; however, the fact that these materials cannot yet be produced in large scale is an obstacle to realize the potential applications of this material. In this respect, chemical methods seem to be efficient synthesis pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
90
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(98 citation statements)
references
References 68 publications
6
90
1
1
Order By: Relevance
“…At higher magnification area a as shown in Figure 6 to the right, there exists well defined loosely packed spherical arrays. Same structure was observed in [26] and [27] where they defined this structure as a function of the increase of the PEG content as a surfactant. It has a great role in obtaining a smooth surface with an increased sphericity in the existing particles.…”
Section: Surface Morphology Through Scanning Electron Microscopy(sem)supporting
confidence: 56%
See 1 more Smart Citation
“…At higher magnification area a as shown in Figure 6 to the right, there exists well defined loosely packed spherical arrays. Same structure was observed in [26] and [27] where they defined this structure as a function of the increase of the PEG content as a surfactant. It has a great role in obtaining a smooth surface with an increased sphericity in the existing particles.…”
Section: Surface Morphology Through Scanning Electron Microscopy(sem)supporting
confidence: 56%
“…Tran et. al in [26] related the presence of agglomerated clusters to the presence of water added to the alcohol as a solvent. According to their theory, the water viscosity is higher than that of the alcohol.…”
Section: Surface Morphology Through Scanning Electron Microscopy(sem)mentioning
confidence: 99%
“…This oxide is a p-type multifunctional semiconductor, which has narrow band gap values (1.2 -1.5 eV) [2][3][4] . Its monoclinic structure presents interesting characteristics, such as, thermal superconductivity, thermal stability 5 , photovoltaic properties and antimicrobial activity 6 . This metal oxide has been extensively investigated in recent years due to several applications such as an electric superconductor 7 , battery electrodes for lithium-ion cell 8 , solar sensors 9 , gas sensors 10 , catalysts 11 and wastewater treatments 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Wang et al [8] reported reducing volatile organic sensing via sol-gel-synthesized CuO nanoparticles. It has been synthesized using numerous techniques such as hydrothermal, physical vapor deposition, sputtering, chemical vapor deposition, and co-precipitation methods [4,6,11]. Among these, the co-precipitation method using the water bath technique, in particular, has the benefit of low-temperature growth, low cost, and a simple process [12].…”
Section: Introductionmentioning
confidence: 99%